Application of Weidenbach and Levine's Conservative Theory to Assessmentabnormal Uterine Bleeding with Hypovolemic Shock - Yayu Handayani Syaidar Putri; Windy Natasha; Restuning Widiasih (Indonesian Journal of Global Health Research, 2024)
Abnormal uterine bleeding (AUB) is a broad term for changes in the regularity, duration or volume of menstrual bleeding. Physical and psychological problems that PUA patients may experience and emergency complications such as hypovolemic shock. Nursing actions that can be taken for PUA patients include comprehensive assessment management. The purpose of this study was to describe the nursing assessment of PUA patients using Levine's conservation theory approach combined with Weidenbach's theory. This study uses a case study method with a focus on the application of Wiedenbach and Levine's theory in providing assessment of PUA patients with anxiety and monitoring physical and psychological aspects. The case studied involved a 15-year-old adolescent with PUA presenting with hypovolemic shock. By applying Wiedenbach's and Levine's conservative theories, nurses can conduct a comprehensive assessment of mothers of PUA patients with hypovolemic shock.